Syntheses and stabilities of proteins related to the polyoma small T antigen in Escherichia coli. - Horwich, A (1982)
We compared the syntheses and turnovers of two proteins related to the polyoma small T antigen synthesized in Escherichia coli from plasmids containing polyoma genomic segments joined to lac control elements. A protein with an authentic polyoma N terminus was more unstable than a protein with N-terminal amino acids derived from beta-galactosidase. Both were more unstable than most bacterial proteins.